Pengaruh Lokasi, Harga dan Cita Rasa Terhadap Kepuasan Pelanggan pada Rumah Makan Lalapan Tanta Anna Tondano - Githa Ils Rumambi; Anggela Aine Adam (Cerdika: Jurnal Ilmiah Indonesia, 2025)
The culinary industry in Indonesia is growing rapidly and facing increasingly fierce competition, making customer satisfaction a crucial factor in maintaining customer loyalty. Lalapan Tanta Anna Tondano Restaurant, which has been operating for over 15 years, was chosen as the research object due to its popularity and the challenges of competition from similar businesses. This study aims to analyze the influence of location, price, and taste on customer satisfaction at Lalapan Tanta Anna Tondano Restaurant. The research method used a quantitative approach using a survey technique using a valid and reliable questionnaire. The study population was the restaurant's customers, with the sample determined using a purposive sampling technique. Data analysis was performed using multiple linear regression to test the effect of the independent variables (location, price, taste) on the dependent variable (customer satisfaction). The results of the study indicate that location, price, and taste have a positive and significant effect on customer satisfaction, both partially and simultaneously. Taste is proven to be the most dominant variable in increasing customer satisfaction and loyalty. The coefficient of determination (R²) indicates that most of the variation in customer satisfaction can be explained by these three variables. The conclusions of this study emphasize the importance of business location management, appropriate pricing, and consistent taste in creating customer satisfaction. These findings provide theoretical contributions to the development of the concept of customer satisfaction and provide practical recommendations for culinary entrepreneurs in improving service quality and business competitiveness.